The design and applications of a recursive molecular modeling framework. - Lisle, C.
In this paper, we present a recursive molecular model that is suitable for multi-resolution analysis in a variety of application areas. Our approach allows ease of use by computer scientists and biologists by proposing a software interface for molecular analysis that hides programming details. We demonstrate that our design is flexible enough for use in desktop analytical applications, in large-scale parallel simulations, and as a server for remote molecular analysis across wide-area networks.
Keywords: Desktop analytical applications; Ease of use; Flexible design; Large-scale parallel simulations; Molecular biology; Molecular dynamics; Multi-resolution analysis; Object-oriented framework; Physical modelling; Programming details; Recursive molecular model; Remote molecular analysis; Server; Software interface; Wide area networks